2019
DOI: 10.25083/rbl/24.5/776.782
|View full text |Cite
|
Sign up to set email alerts
|

A physico - chemical characterization of oil from Camelina sativa seeds grown in Romania

Abstract: It is well-known that camelina oil, obtained from Camelina sativa seeds is rich in fatty acids, predominantly linolenic acid and is used successfully in pharmaceutical and cosmetic therapies. It is remarkable that this species has a great adaptability to environmental conditions, being able to cultivate it on agricultural parcels and polluted soils. The goal of this work is to evaluate the quantitative and qualitative differences of three types of camelina oils, obtained from varieties grown in Romania: GP 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
4
3
0
Order By: Relevance
“…Camelina sativa oil is rich in vitamins, UFAs, phytosterols, and polyphenols (Kurasiak‐Popowska & Stuper‐Szablewska, 2020 ). In accordance with our results and those of other authors, the dominant FAs in camelina oil are UFAs, MUFAs, and mostly PUFAs (>55%), SFAs ranging from 9.1% to 10.8% (Popa, et al, 2021 ). The most frequent FAs identified in camelina oil are linolenic (on average, 35%), linoleic (on average, 20.5%), oleic (on average, 16%), and eicosenoic (on average, 17%) (Popa, et al, 2021 ).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Camelina sativa oil is rich in vitamins, UFAs, phytosterols, and polyphenols (Kurasiak‐Popowska & Stuper‐Szablewska, 2020 ). In accordance with our results and those of other authors, the dominant FAs in camelina oil are UFAs, MUFAs, and mostly PUFAs (>55%), SFAs ranging from 9.1% to 10.8% (Popa, et al, 2021 ). The most frequent FAs identified in camelina oil are linolenic (on average, 35%), linoleic (on average, 20.5%), oleic (on average, 16%), and eicosenoic (on average, 17%) (Popa, et al, 2021 ).…”
Section: Resultssupporting
confidence: 94%
“…In accordance with our results and those of other authors, the dominant FAs in camelina oil are UFAs, MUFAs, and mostly PUFAs (>55%), SFAs ranging from 9.1% to 10.8% (Popa, et al, 2021 ). The most frequent FAs identified in camelina oil are linolenic (on average, 35%), linoleic (on average, 20.5%), oleic (on average, 16%), and eicosenoic (on average, 17%) (Popa, et al, 2021 ). Ratusz et al (Ratusz et al., 2018 ) analyzed 29 cold‐pressed camelina oils and determined a highly optimal n‐3 PUFA to n‐6 PUFA ratio (1.79–2.17).…”
Section: Resultssupporting
confidence: 94%
“…In the camelina seed OBs, the concentration of erucic acid (22:1 n-9) was 2.34%, in agreement with data reported for camelina seed oil [53]. Camelina seed oil has a lower content of erucic acid (1.6-4.2%) compared with other oils of cruciferous species [54]. SDS-PAGE allowed the identification of the proteins contained in the aqueous extracts and of those specifically localised at the surface of the chia and camelina seed OBs (Figure 3F).…”
Section: Fatty Acid Compositionsupporting
confidence: 88%
“…In the camelina seed OBs, the concentration of erucic acid (22:1 n-9) was 2.34%, in agreement with data reported for camelina seed oil [53]. Camelina seed oil has a lower content of erucic acid (1.6-4.2%) compared with other oils of cruciferous species [54]. The total PUFA accounted for 82.1 ± 0.2% in chia seed OBs and 55.0 ± 0.1% in camelina seed OBs.…”
Section: Fatty Acid Compositionsupporting
confidence: 88%
“…[18] Other researchers presented a similar level of camelina oil hydrolysis. The research conducted by Popa et al [19] showed a similar and higher AV of cold-pressed camelina oil, which was from 0.63 to 4.61 mg KOH g −1 . Marszałkiewicz et al [20] determined its level from 0.67 to 6.87 mg KOH g −1 .…”
Section: The Initial Quality Of Analyzed Camelina and Hemp Seed Oilsmentioning
confidence: 76%